Newspaper Use of a University's Regional Farm Column - Gordon Billingsley (Journal of Applied Communications, 1983)
You can ask any county farm agent how to get local farm columns published: write about local persons and events. Content newspapers have shown that local information is crucial to the success of local farm columns.